Evaluation of the efficiency of use of aggregates and chemical compounds for winter road maintenance - Kołodziejczyk, Urszula; Ćwiąkała, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this article is to indicate the most effective chemical agents used for winter road maintenance. The research included the examination of melting speeds of snow and ice under various chemical agents, such as: calcium chloride, sodium chloride, potassium chloride and potassium formate. The research done proved that aggregate mixed with calcium chloride is the most efficient compound for removing winter road slipperiness. However, in view of the necessity of environmental protection, the use of chemical agents for maintaining roads during winter must be strictly controlled in practice.
Keywords: zimowe utrzymanie dróg; środki chemiczne; winter road maintenance; chemical compounds